Biomedical Academic Entrepreneurship Through the SBIR Program - Andrew A. Toole; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper considers the U.S. Small Business Innovation Research (SBIR) program as a policy fostering academic entrepreneurship. We highlight two main characteristics of the program that make it attractive as an entrepreneurship policy : early-stage financing and scientist involvement in commercialization. Using unique data on NIH supported biomedical researchers, we trace the incidence of biomedical entrepreneurship through SBIR and describe some of the characteristics of these individuals. To explore the importance of early-stage financing and scientist involvement, we complement our individual level data with information on scientist-linked and non-linked SBIR firms. Our results show that the SBIR program is being used as a commercialization channel by academic scientists. Moreover, we find that the firms associated with these scientists perform significantly better than other non-linked SBIR firms in terms of followon venture capital funding, SBIR program completion, and patenting.
Keywords: C25; O38; O31; M13; G38; 330; Academic entrepreneurship; star scientists; SBIR; Venture Capital; innovation; Hochschulforschung; Biotechnische Forschung; Medizin; Unternehmensgründung; Unternehmer; Gewerbepolitik; USA